Guest

Add: 4x2 y, – 3xy2 , –5xy2 , 5x2 y Add: 4x2 y, – 3xy2 , –5xy2 , 5x2 y

Add: 
4x2 y, – 3xy2 , –5xy2 , 5x2 y
Add: 
4x2 y, – 3xy2 , –5xy2 , 5x2 y

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5963 Points
3 years ago
Dear Student

When term have the same algebraic factors, they are like terms. Then, we have to add the like terms
= 4x^2y + (-3xy^2) + (-5xy^2) + 5x^2y
= 4x^2y + 5x^2y–3xy^2–5xy^2
= x^2y (4 + 5) + xy^2(-3 - 5)
= x^2y (9) + xy^2(- 8)
= 9x^2y–8xy^2

Thanks

Think You Can Provide A Better Answer ?

ASK QUESTION

Get your questions answered by the expert for free